A method for determination of thermodynamic and solubility parameters of polymers from temperature and molecular weight dependence of intrinsic viscosity - Bozdogan, AE (ELSEVIER SCI LTD, 2004)
An equation using the temperature dependence of intrinsic viscosity of a polymer was proposed for the determination of the partial molar entropy and enthalpy changes of the polymer for mixing in dilute solution. It was found that the partial molar entropy change of a polymer for mixing at a given temperature is proportional to the hydrodynamic volume or segment number of the polymer. The partial molar enthalpy change of the polymer for mixing was determined from the thermodynamic equilibrium property of polymer phases. The solubility or cohesion parameter of a polymer fraction was calculated by using the partial molar enthalpy change and repeat unit volume of the polymer. The solubility parameter of high molar mass polymer at a given temperature was determined by extrapolating solubility parameter values of polymer fractions to high molar mass by using the solubility parameter-segment number relation of polymer fraction. This relation gives a straight line. The solubility parameter of the polymer at a given temperature and the effective interchange energy parameter for polymer-solvent pair were obtained directly from the intercept and the slope of this line, respectively. These equations were applied to the intrinsic viscosity-temperature data of polystyrene fractions in decalin solutions, and polystyrene fractions in decalin, cyclohexane and dioctyl phthalate solutions at the theta temperatures and in toluene solutions at the given temperatures. The results obtained in this study coincide with the literature values. In addition, it was given a relation, which is derived from the blob theory for the temperatures above the theta point, for the estimation of the thermodynamic parameters of polymers for mixing. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: intrinsic viscosity-temperature relation and thermodynamic parameters; solubility parameter-segment number relation; the blob theory and thermodynamic parameters; POLYSTYRENE SOLUTIONS; DILUTE-SOLUTIONS; THETA; Polymer Science